KAJIAN KESEJAHTERAAN HARIMAU SUMATERA PADA KONSERVASI EX-SITU DI TAMAN MARGASATWA RAGUNAN DAN TAMAN MARGASATWA BANDUNG - Yolanda, Yolanda; Rusdi, Rusdi; Supiyani, Atin (Bioma, 2017)
A zoo is one of an ex-situ conservation activity whice aimed to conserve plants and wildlife animal an endangered position, for example; the Panthera tigris sumatrae population are decrease. The zoo were succeed to captivate an animal only if they can adopt their normal life into that place. The aim of this research was to study the animal welfare from Sumatran tiger in two different places; Bandung zoo and Ragunan zoo. This research has been conducted in Desember – February 2017. The research method that are used in this study were interviewed and filling draft animal welfare from Indonesian Ministry of Forest No.P.9/VI-SET/2011. The Result of this research were 77% point for Ragunan zoo and 60% point for Bandung zoo which different mean both of that place. Filling draft animal welfare consist beside five freedom of animal welfare; 1). Freedom from hunger and thirst, 2). Freedom from discomfort, 3). Freedom from injury, paint, and disease, 4). Freedom to express natural behavior, 5). Freedom from fear and distress. The conclusion of this research were Ragunan zoo was better than Bandung zoo to applied animal welfare rules.